2019
DOI: 10.1021/acsbiomaterials.9b00499
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial and Connective Tissue Sealing around Titanium Implants with Various Typical Surface Finishes

Abstract: Soft tissue barrier around a dental implant plays a crucial role in the success of dental implants because it protects underlying hard tissue structures. A number of surface alteration procedures of implants have been introduced to improve bone−implant contact, but there has been little research on the peri-implant soft tissue (PIS) seal. The present study focuses on the "biologic width" of epithelial and connective tissue seals around implants with various typical surface finishes by testing surfaces that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…In our animal study, there was no statistically significant difference in the length of the Inβ4-positive band between Ti and zirconia groups, both of which were significantly shorter than that for teeth. As previously reported, the length of the laminin-332-postive band on the substratum side of the attachment structure was significantly shorter around Ti than that around teeth [ 7 , 11 ]. The present study showed that the localization of Inβ4 on the cell side of the attachment structure was similar to that of laminin-332.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In our animal study, there was no statistically significant difference in the length of the Inβ4-positive band between Ti and zirconia groups, both of which were significantly shorter than that for teeth. As previously reported, the length of the laminin-332-postive band on the substratum side of the attachment structure was significantly shorter around Ti than that around teeth [ 7 , 11 ]. The present study showed that the localization of Inβ4 on the cell side of the attachment structure was similar to that of laminin-332.…”
Section: Discussionsupporting
confidence: 62%
“…The attachment structure between the gingival epithelium and substrata such as enamel or implants comprises two components, namely basal lamina and cell-adhesion protein. Previous studies indicated that the length of the band of laminin-332, which is a main component of basal lamina, is shorter around Ti implants than around the enamel [ 7 , 11 ]. In contrast, another component of the attachment structure, transmembrane receptors in epithelial cells, has not yet been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations